Pengelolaan Media Pembelajaran Berbasis Information Technology (It) Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah Menengah Kejuruan Al Alif Blora Tahun 2015 - Nurdhuka, Moh (2016)
The purpose of this study was to describe the use of media-based learning Planning IT, implementation and evaluation of instructional media usage of IT based learning on the subjects of PAI in SMK Al Alif Blora. This study is a qualitative research approach Ethnography. This research was conducted in SMK Al Alif Blora. Data collected by 1) intent interviews, 2) observation, 3) documentation. Data analysis was performed with data reduction, data presentation and conclusion. The validity of the data is tested using triangulation techniques, the source and method triangulation. Results of the study were 1) Planning instructional media management carried out independently by the teacher of Islamic education in schools, to realize the main factors that need to be considered in the planning of instructional media. Planning involves the preparation of lesson plan, syllabus and learning tools, preparation of media tools that are already available in school, that as an example of religious practice rooms, projectors, TV, VCD, computers, and networks wifi / Blog. To overcome the obstacle PAI teacher always ask for advice and guidance from all parties involved. 2) The process of implementation in the management of IT based instructional media on subjects PAI at SMK Al Alif Blora refers to the planning results. All activities are performed by teacher charged with the responsibility to process and apply the tools of the media with the best in class with the adjustment between the media with material and needs of the students are many and diverse. 3) The evaluation is done regularly by PAI teachers in activities in using media not only to examine the implementation of activities, but also how the process of planning and analysis of the results of evaluation to improve and enhance media management with the availability of tests to be performed or answered by students both through oral (frequently asked questions) and written as feedback Keywords: Management, IT based learning media, teachers, learners